Enhancing Students’ Speaking Skill through the Show and Tell Technique - Wardani, Marshela (Institut Agama Islam Negeri (IAIN) Kediri, 2024)
Speaking is critical for junior high school students alongside listening, reading, and writing. However, problems in teaching speaking, such as limited vocabulary and low participation rates, expectedly emerged as observed at an Islamic junior high school. This study explores the effectiveness of the